A study of Shiba Taraz's Travelogue "Europe main 19 din" - Liaqat, Mr.; Fatima, Sadaf; Parveen, Nazia (sourcecoder, 2022)
Shiba Traz is a versatile personality in Urdu literature. she is known as a writer, poete, artist and an intelligent journalist in academic, literary and social circles. Her father is Syed Asghar Mehdi and mother is Uzra Asghar. She has only one brother Syed Anber Tajoor. She got her education up to BSC as regular student. Later she was married to Zaigham Abbas n did her MA in Urdu as a private candidate. She has three daughters. She is editor of literary magazine Tagdeed e no published from Lahore and also she is honorary editor of a magazine “Makhzan” published from England. She is a member of Halqa e arbab e zoq. She inherited the literary taste while she is a born artist. This artistic touch reflects through her literary pieces. Sheepberry, stories, travelogue, and translations have Captivated the interest of the readers